2021
DOI: 10.7759/cureus.16922
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Direct Acting Oral Anticoagulants in Cirrhotic and Non-Cirrhotic Portal Vein Thrombosis: A Systematic Review

Abstract: Thrombosis of the portal vein (PVT) is generally seen in the setting of liver cirrhosis and to a lesser extent in the absence of cirrhosis. There is no clear guidance in relation to approaching treatment with anticoagulation in this condition. The professional societies and guidelines recommend treatment with traditional anticoagulation like low-molecular-weight heparin and vitamin-K antagonists in patients presenting with acute portal vein thrombosis. There is no clarity in relation to treatment in the settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In two studies on large cohorts of IBD patients with a follow-up time over 10 years, thromboembolic complications were reported in about 1% of patients, with an incidence of VTE of 2.6/1000 persons/year[ 85 , 86 ]. Porto-mesenteric venous system is a frequent site of thrombosis in IBD and is a potentially catastrophic complication, which may lead to bowel ischemia or infarction and to acute or chronic portal hypertension; the mortality rate range between 3%-25%[ 86 , 87 ]. Incidence is higher during disease flares and after surgical procedures[ 88 - 90 ], and prophylactic treatment with low-molecular-weight heparin in severely active disease is indicated by guidelines to reduce the risk of thromboembolism[ 91 ].…”
Section: Non-immune-mediated Disordersmentioning
confidence: 99%
“…In two studies on large cohorts of IBD patients with a follow-up time over 10 years, thromboembolic complications were reported in about 1% of patients, with an incidence of VTE of 2.6/1000 persons/year[ 85 , 86 ]. Porto-mesenteric venous system is a frequent site of thrombosis in IBD and is a potentially catastrophic complication, which may lead to bowel ischemia or infarction and to acute or chronic portal hypertension; the mortality rate range between 3%-25%[ 86 , 87 ]. Incidence is higher during disease flares and after surgical procedures[ 88 - 90 ], and prophylactic treatment with low-molecular-weight heparin in severely active disease is indicated by guidelines to reduce the risk of thromboembolism[ 91 ].…”
Section: Non-immune-mediated Disordersmentioning
confidence: 99%
“…Dr Abd-Elsalam's COVID-19 RCTs have garnered nearly 1,000 citations in total and been included in a large number of systematic reviews and clinical practice guidelines. (21)(22)(23) Dr Abd-Elsalam's work prior to the pandemic has also been highly influential, for example Hanafy2019a, an RCT of rivaroxaban and warfarin for portal vein thrombosis that has been cited over 100 times and included in six systematic reviews (24)(25)(26)(27)(28)(29). As a consequence, inappropriate practice recommendations may have been drawn, and inappropriate treatments could have been offered to patients.…”
Section: Discussionmentioning
confidence: 99%
“…DOACs such as rivaroxaban, apixaban, or dabigatran have not been well studied in this patient population. However, a recent systematic review showed that DOACs appear to be a promising choice for the treatment of patients with PVT [29]. Anticoagulation therapy in non-cirrhotic chronic PVT has a controversial role [1][2][3]28].…”
Section: Discussionmentioning
confidence: 99%